A samarium cobalt permanent magnetic material and its preparation method and application

By adjusting the FE content and the content of rare earth elements in the SM2CO17 permanent magnet material, and using a specific timeliness processing process, it is difficult to form a uniform organizational structure when the FE content is high, and the high -performance martial arts permanent magnet material is achieved.

CN114267509BActive Publication Date: 2025-01-28FUJIAN CHANGTING ZORR TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111444479.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-30
Publication Date
2025-01-28
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

When the Fe content of the existing Sm2Co17 permanent magnet material is high, it is difficult to form a uniform and complete cellular tissue structure, resulting in deterioration of magnetic properties.

Method used

By adjusting the FE content to 20-25WT %, combined with the preferred content of rare earth element RE, and using specific timeliness processing processes, including pre-efficiency and first-level timeliness, to form a uniform and complete cell-shaped tissue structure and maze-shaped magnetic domain structure structure Essence

Benefits of technology

The continuous adjustment of the remaining magnetic is between 11.90-12.40kgs, which improves the remaining magnetic, orthopedic, magnetic energy accumulation, square form, remaining magnetic temperature coefficient and stubborn temperature coefficient of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114267509B_ABST
    Figure CN114267509B_ABST
Patent Text Reader

Abstract

The invention discloses a samarium cobalt permanent magnet material and a preparation method and application thereof. The preparation method of the samarium cobalt permanent magnet material comprises the following steps: forming, sintering, aging treatment and heat preservation of samarium cobalt magnet alloy powder; in the aging treatment, the pre-aging temperature is 650-750°C and the time is 2-5h; the primary aging temperature is T=(M1×a+N1)°C; M1 is 19.95-20.05; N1 is 445-455; a is the value obtained by multiplying the Fe content by 100; the primary aging time is t=(M2×T+N2)min; M2 is (-9.95)-(-10.05); N2 is 9695-9705. The samarium cobalt permanent magnet material of the invention can realize continuous adjustable remanence when the Fe content is as high as 20-25wt%, and has a better magnetic domain structure, thereby improving the remanence, coercive force, magnetic energy product, squareness and temperature coefficient of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a samarium cobalt permanent magnetic material and a preparation method and application thereof. Background Art

[0002] Sm2Co 17 The magnetic properties of permanent magnet materials are closely related to the Fe content contained in their formula. Therefore, the industry usually adjusts the Fe content to control the magnetic properties to obtain products of different grades. However, the performance of samarium cobalt magnets is also closely related to their heat treatment process, and the heat treatment process, especially the aging process, is extremely sensitive to the Fe content of the formula. In theory, the higher the Fe content, the higher the remanence and magnetic energy product of the product. However, as the Fe content increases, the phase changes become more complex, and it becomes more difficult to form a uniform and complete cellular structure during the aging process, thereby deteriorating the magnetic properties. Therefore, how to adjust the appropriate heat treatment process according to the Fe content is a major problem in the preparation of high-grade samarium cobalt materials. Summary of the invention

[0003] The present invention aims to solve the problem of Sm2Co 17 When the Fe content in the permanent magnet material is high, it is difficult to form a uniform and complete cellular structure, thereby deteriorating the magnetic properties. A samarium cobalt permanent magnet material and a preparation method and application thereof are provided. 17 The permanent magnet material can achieve a continuously adjustable remanence between 11.90-12.40 kGs when the Fe content is as high as 20-25 wt%. 17 The permanent magnet material has a better magnetic domain structure, avoiding the generation of uneven large magnetic domains, thereby improving the product's remanence, coercivity, magnetic energy product, squareness, remanence temperature coefficient and coercivity temperature coefficient.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions provided by the present invention is:

[0006] A method for preparing a samarium-cobalt permanent magnetic material comprises the following steps: molding, sintering, aging treatment and heat preservation of samarium-cobalt magnet alloy powder;

[0007] In the samarium-cobalt magnet alloy powder, the content of Fe is 20-25wt%, and the content of the rare earth element Re is not less than 23wt%, and the percentage is the mass percentage of the Fe or the rare earth element Re in the samarium-cobalt magnet alloy powder;

[0008] The rare earth element includes one or more of Sm, Pr and Nd;

[0009] The aging treatment includes pre-aging and primary aging;

[0010] The pre-aging temperature is 650-750°C; the pre-aging time is 2-5h;

[0011] The primary aging temperature is T = (M1 × a + N1) ° C; wherein M1 is 19.95-20.05; N1 is 445-455; a is the value obtained by multiplying the Fe content by 100, that is, a = 20-25;

[0012] The time of the primary aging is t=(M2×T+N2)min; M2 is (-9.95)-(-10.05); N2 is 9695-9705; T is the temperature of the primary aging.

[0013] In the present invention, the content of Fe is preferably 20wt%, 20.5wt%, 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt%, 24.5wt% or 25wt%.

[0014] In the present invention, the content of the rare earth element Re is preferably 24-26wt%, for example, 24wt%, 24.2wt%, 24.5wt%, 24.7wt%, 25wt%, 25.2wt%, 25.3wt%, 25.4wt%, 25.6wt%, 25.8wt% or 26wt%.

[0015] In the present invention, the rare earth element preferably includes Sm, or Sm and Pr, or Sm and Nd.

[0016] Among them, the Sm content is preferably greater than 23wt%, for example, 23.2wt%, 24wt%, 24.2wt%, 24.5wt%, 24.7wt%, 25wt%, 25.2wt%, 25.3wt%, 25.4wt%, 25.6wt%, 25.8wt% or 26wt%.

[0017] Wherein, the content of Pr is preferably 1wt%.

[0018] Wherein, the content of Nd is preferably 1wt% or 2wt%.

[0019] In the present invention, the Cu content in the samarium cobalt magnet alloy powder may be 4.0-6.0wt%, for example, 4.5wt%, 4.8wt%, 5.1wt%, 5.2wt%, 5.4wt%, 5.5wt%, 5.6wt% or 5.8wt%, where the percentage is the mass percentage of the Cu in the samarium cobalt magnet alloy powder.

[0020] In the present invention, the Zr content in the samarium cobalt magnet alloy powder may be 3-4.5wt%, for example, 3.2wt%, 3.4wt%, 3.5wt%, 3.55wt%, 3.6wt%, 3.65wt%, 3.7wt%, 3.9wt%, 4.2wt% or 4.5wt%, where the percentage is the mass percentage of the Zr in the samarium cobalt magnet alloy powder.

[0021] In the present invention, the content of Co in the samarium cobalt magnet alloy powder can be the balance, generally 40-50%, preferably 42-45wt%, for example, 42.3wt%, 42.5wt%, 42.9wt%, 42.95wt%, 43.1wt%, 43.65wt%, 44.2wt% or 44.7wt%, where the percentage is the mass percentage of the Co in the samarium cobalt magnet alloy powder.

[0022] The "remainder" does not exclude other elements, such as Nd or Pr, that may be included in the samarium-cobalt magnet alloy powder in addition to the elements mentioned in the present invention. When the samarium-cobalt magnet alloy powder also includes other elements in addition to the elements mentioned in the present invention, the amount of Co is adjusted accordingly so that the mass percentage of the elements other than Co in the samarium-cobalt magnet alloy powder is within the range defined in the present invention.

[0023] In the present invention, the samarium cobalt magnet alloy powder can be prepared according to conventional methods in the art, for example, the raw materials of samarium cobalt permanent magnet material are smelted and crushed to obtain the samarium cobalt magnet alloy powder.

[0024] The smelting method may be conventional in the art, such as a belt casting method, centrifugal casting or ingot casting method.

[0025] The crushing method may be conventional in the art, generally including coarse crushing, medium crushing and fine crushing. The coarse crushing may include jaw crushing. The medium crushing may include crushing with a medium crusher and / or crushing with a disc mill. The fine crushing may include crushing with a jet mill and / or crushing with a ball mill.

[0026] After the samarium-cobalt magnet alloy powder is jet milled or ball milled, the average particle size D50 can be 4-6 μm.

[0027] In the present invention, the molding operation and conditions may be conventional in the art, and preferably, the oriented compression molding is performed in a constant magnetic field.

[0028] Wherein, the forming magnetic field strength B is preferably 1.5-2T.

[0029] In the present invention, the sintering operation and conditions may be conventional in the art.

[0030] The sintering is preferably carried out in an inert atmosphere, the sintering temperature is preferably 1200 to 1220° C., and the sintering time is preferably 2 to 5 hours.

[0031] In the present invention, the sintering preferably further includes solid solution.

[0032] The temperature of the solid solution is preferably 1140 to 1190° C. The time of the solid solution is preferably 1 to 40 hours.

[0033] After the solid solution, a solid solution blank of the samarium cobalt permanent magnet material can generally be obtained.

[0034] In the present invention, preferably, the primary aging temperature is T=(M1×a+N1)°C, wherein M1 is 20 and N1 is 450.

[0035] More preferably, the primary aging temperature is T=(20×a+450)°C.

[0036] In the present invention, preferably, the primary aging time is t=(M2×T+N2) min; M2 is -10.00; N2 is 9700; and T is the primary aging temperature.

[0037] More preferably, the primary aging time is t=(-10×T+9700) min.

[0038] In the present invention, the insulation temperature may be 390-420° C., preferably 400° C. The insulation time may be 5-10 hours. Preferably, the rate of decreasing from the primary aging temperature to the insulation temperature is 0.7° C. / min.

[0039] The second technical solution provided by the present invention is: a samarium cobalt permanent magnet material, which is prepared by the preparation method of the samarium cobalt permanent magnet material as described above.

[0040] The third technical solution provided by the present invention is: a samarium cobalt permanent magnet material, in which a uniform and complete cellular organizational structure is formed, and a uniform and fine strip-shaped magnetic domain structure is provided; the interior of the strip-shaped magnetic domain structure is in a maze shape.

[0041] Wherein, the domain width of the strip-shaped magnetic domain structure may be 1.8-2.2 μm, for example, 1.9 μm, 2.0 μm or 2.1 μm.

[0042] Preferably, the preparation method of the samarium cobalt permanent magnet material is as described above.

[0043] The fourth technical solution provided by the present invention is: an application of the samarium cobalt permanent magnet material as described above in the preparation of electronic communication equipment, aerospace equipment or rail transportation equipment.

[0044] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0045] The reagents and raw materials used in the present invention are commercially available.

[0046] The positive and progressive effect of the present invention is that the present invention systematically studies the samarium cobalt permanent magnet material with an Fe content range of 20-25wt%, and adopts the preparation method of the present invention to adjust the Fe content to make the remanence reach 11.90-12.40kGs, and it is continuously adjustable between 11.90-12.40kGs. At the same time, according to the formula of the present invention, a suitable aging treatment process is selected, and the prepared samarium cobalt permanent magnet material has a uniform and complete cellular organizational structure, and has a uniform and fine strip-shaped maze-type magnetic domain structure (domain width is 1.8-2.2μm). Furthermore, the Hcb value of the samarium cobalt permanent magnet material in the present invention is as high as 10.90-11.35kOe, the coercive force is as high as 25kOe or more (25-32kOe), the magnetic energy product is 33-35MGOe, the squareness is more than 61.4% (61.4-67.2%), the remanence temperature coefficient α is (-0.03)%-(-0.04)%, and the coercive force temperature coefficient β is (-0.20)~(-0.35)%.

[0047] The samarium cobalt permanent magnet material in the present invention can meet the production requirements of high-performance samarium cobalt magnets, has excellent room temperature and high temperature magnetic properties, has obvious advantages over neodymium iron boron high-performance products at high temperature (150°C), and can be used in the motor field as a substitute for neodymium iron boron. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a control curve diagram of the Fe content and remanence of the samarium cobalt permanent magnet material in Examples 1, 3, 5, 7, 9, and 11.

[0049] Figure 2 It is a magnetic property curve diagram of the samarium cobalt permanent magnet material in comparative examples 8, 9, 10 and embodiment 5.

[0050] Figure 3 These are magneto-optical Kerr microscope observation images of the magnetic domains of the samarium cobalt permanent magnet materials in comparative examples 8, 9, 10 and embodiment 5.

[0051] Figure 4 This is a scanning electron microscope image of the distribution of Cu element in the samarium cobalt permanent magnet material of Example 5.

[0052] Figure 5 This is a comparison chart of the magnetic energy product of the samarium cobalt permanent magnet material and the neodymium iron boron material at different temperatures in Example 5.

[0053] Figure 6 This is the magnetic property test curve of the samarium cobalt permanent magnet material in Example 5 at different temperatures. DETAILED DESCRIPTION

[0054] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0055] Examples 1 to 14 and Comparative Examples 1 to 10

[0056] (1) Smelting and crushing the raw materials of the samarium-cobalt magnet alloy powder shown in Table 1 to obtain the samarium-cobalt magnet alloy powder, wherein the particle size D50 of the samarium-cobalt magnet alloy powder is 4-6 μm;

[0057] Among them, smelting adopts the belt throwing method, centrifugal casting or ingot casting method; crushing is coarse crushing, medium crushing and fine crushing in sequence; coarse crushing is jaw crushing; medium crushing is crushing by medium crusher or disc mill; fine crushing is air flow mill.

[0058] (2) forming, sintering, solid solutionizing, pre-aging, primary aging and heat preservation the samarium-cobalt magnet alloy powder obtained in step (1);

[0059] The oriented pressing molding is carried out in a constant magnetic field. The magnetic field strength, sintering temperature and time, solution temperature and time, pre-aging time and temperature, primary aging temperature and time, and insulation temperature and time are shown in Table 2. The rate of decreasing from the primary aging temperature to the insulation temperature is 0.7°C / min.

[0060] Table 1

[0061]

[0062]

[0063] Table 2

[0064]

[0065]

[0066] Effect Example

[0067] (1) Magnetic property detection

[0068] The magnetic properties of the samarium cobalt permanent magnet materials in the embodiments of the present invention and the comparative examples were tested using a pulsed magnetic field meter PFM. The results of the remanence Br, magnetic coercivity Hcb, intrinsic coercivity Hcj, squareness Hk / Hcj, remanence temperature coefficient α, coercivity temperature coefficient β and magnetic energy product (BH) max are shown in Table 3.

[0069] Table 3

[0070]

[0071]

[0072] From Table 3 and Figure 1 It can be seen that the Fe content of the samarium cobalt permanent magnet material in Examples 1, 3, 5, 7, 9 and 11 is in the range of 20-25wt%, and the remanence thereof is continuously adjustable between 11.90-12.40 kGs.

[0073] The angle between the magnetic performance curve and the horizontal axis (θ J ) and the domain width of the stripe magnetic domain structure, as shown in Table 4.

[0074] Table 4

[0075]

[0076]

[0077] It can be seen from Tables 3 and 4 that the angle (θ J ) is closer to a right angle (e.g. 80-90°), the higher the squareness of the samarium cobalt permanent magnet material.

[0078] The magnetic property curve of the samarium cobalt permanent magnet material in Example 5 is as follows: Figure 2 As shown in D, the angle (θ J ) is close to a right angle (90°), and according to Figure 3 As shown in B (the scale in the magnetic domain diagram is 50 μm), the samarium cobalt permanent magnet material has a uniform and fine (about 2 μm) strip-shaped magnetic domain structure, and the interior of the strip-shaped magnetic domain structure is maze-shaped.

[0079] The magnetic property curve of the samarium cobalt permanent magnet material in Comparative Example 8 is as follows: Figure 2 As shown in Figure A, due to the short primary aging time, its coercivity is very low (obviously less than 10kOe), and the squareness of the magnetic property curve is very poor, showing an S shape, and the BH line is curved; in addition, according to Figure 3 As shown in A (the scale in the magnetic domain diagram is 50 μm), the magnetic domain structure of the samarium cobalt permanent magnet material is a coarse strip-shaped maze-shaped magnetic domain. At the same time, when the primary aging temperature is too low, the squareness and coercive force effects are poor, which is the same as comparative example 8.

[0080] The magnetic property curve of the samarium cobalt permanent magnet material in Comparative Example 9 is as follows: Figure 2 As shown in B, due to the long primary aging time, although the coercivity is high, the squareness is significantly reduced (θ J <80°); and, if Figure 3As shown in C (the scale in the magnetic domain diagram is 50 μm), the magnetic domain of the samarium cobalt permanent magnet material begins to have a large non-uniform structure. At the same time, when the primary aging temperature is too high, the squareness effect is poor, which is the same as the comparative example 9.

[0081] The magnetic property curve of the samarium cobalt permanent magnet material in Comparative Example 10 is as follows: Figure 2 As shown in C, due to the lack of pre-aging process, the squareness is low (θ J <80°); and, if Figure 3 As shown in D (the scale in the magnetic domain diagram is 50 μm), the magnetic domains of samarium cobalt permanent magnet materials always have large-scale uneven structures, which cannot be improved by adjusting time and temperature.

[0082] Figure 4 This is a scanning diagram of the Cu element distribution in the samarium cobalt permanent magnet material of Example 5; Figure 4 A is a solid solution, Figure 4 B is the intermediate after primary aging. It can be seen that after primary aging, the Cu element has formed a strip-shaped nano-enriched area, such as Figure 4 The wireframe shown in B.

[0083] It can be seen from the above effect data that the samarium cobalt permanent magnet material in the embodiment has excellent room temperature and high temperature magnetic properties. Figure 5 As shown, taking the high-performance samarium cobalt permanent magnet material in Example 5 as an example, its magnetic energy product at high temperature (150°C) has obvious advantages over NdFeB 35EH and N42EH products, so it can be used in the motor field as a substitute for NdFeB.

[0084] The magnetic performance test curves of the product of Example 5 at different temperatures are as follows: Figure 6 As shown by Figure 6 It can be seen that within the test temperature range of 20-150℃, the magnetic properties show a uniform linear change, and the BH curve remains a straight line at high temperatures without any irreversible changes.

Claims

1. A method for preparing a samarium cobalt permanent magnet material, characterized in that: The preparation method of the samarium cobalt permanent magnet material comprises the following steps: molding, sintering, aging treatment and heat preservation of samarium cobalt magnet alloy powder; In the samarium-cobalt magnet alloy powder, the content of Fe is 20-25wt%, and the content of the rare earth element Re is not less than 23wt%, and the percentage is the mass percentage of the Fe or the rare earth element Re in the samarium-cobalt magnet alloy powder; the rare earth element includes one or more of Sm, Pr and Nd; The aging treatment includes pre-aging and primary aging; The pre-aging temperature is 650-750°C; the pre-aging time is 2-5h; The primary aging temperature is T = (M1 × a + N1) ° C; wherein M1 is 19.95-20.05; N1 is 445-455; a is the value obtained by multiplying the Fe content by 100, that is, a = 20-25; The time of the primary aging is t=(M2×T+N2)min; wherein, M2 is (-9.95)-(-10.05); N2 is 9695-9705; and T is the temperature of the primary aging.

2. The method for preparing the samarium cobalt permanent magnetic material according to claim 1, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The content of Fe is 20.5wt%, 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt% or 24.5wt%; (2) The content of the rare earth element Re is 24-26wt%; (3) The rare earth element includes Sm, or Sm and Pr, or Sm and Nd; (4) The Sm content is greater than 23wt%; (5) The content of Pr is 1 wt%.

3. The method for preparing the samarium cobalt permanent magnetic material according to claim 2, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The content of the rare earth element Re is 24.2wt%, 24.5wt%, 24.7wt%, 25wt%, 25.2wt%, 25.3wt%, 25.4wt%, 25.6wt% or 25.8wt%; (2) the content of Sm is 23.2wt%, 24wt%, 24.2wt%, 24.5wt%, 24.7wt%, 25wt%, 25.2wt%, 25.3wt%, 25.4wt%, 25.6wt%, 25.8wt% or 26wt%; (3) The Nd content is 1wt% or 2wt%.

4. The method for preparing the samarium cobalt permanent magnetic material according to any one of claims 1 to 3, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The content of Cu in the samarium-cobalt magnet alloy powder is 4.0-6.0wt%, and the percentage is the mass percentage of Cu in the samarium-cobalt magnet alloy powder; (2) The content of Zr in the samarium-cobalt magnet alloy powder is 3-4.5wt%, where the percentage is the mass percentage of Zr in the samarium-cobalt magnet alloy powder; (3) In the samarium-cobalt magnet alloy powder, the content of Co is 40-50%, where the percentage is the mass percentage of the Co in the samarium-cobalt magnet alloy powder.

5. The method for preparing the samarium cobalt permanent magnetic material according to claim 4, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) In the samarium cobalt magnet alloy powder, the content of Cu is 4.5wt%, 4.8wt%, 5.1wt%, 5.2wt%, 5.4wt%, 5.5wt%, 5.6wt% or 5.8wt%, where the percentage is the mass percentage of the Cu in the samarium cobalt magnet alloy powder; (2) In the samarium cobalt magnet alloy powder, the content of Zr is 3.2wt%, 3.4wt%, 3.5wt%, 3.55wt%, 3.6wt%, 3.65wt%, 3.7wt%, 3.9wt% or 4.2wt%, where the percentage is the mass percentage of the Zr in the samarium cobalt magnet alloy powder; (3) In the samarium-cobalt magnet alloy powder, the content of Co is 42-45wt%, where the percentage is the mass percentage of Co in the samarium-cobalt magnet alloy powder.

6. The method for preparing the samarium cobalt permanent magnetic material according to claim 5, characterized in that: In the samarium cobalt magnet alloy powder, the content of Co is 42.3wt%, 42.5wt%, 42.9wt%, 42.95wt%, 43.1wt%, 43.65wt%, 44.2wt% or 44.7wt%, where the percentage is the mass percentage of the Co in the samarium cobalt magnet alloy powder.

7. The method for preparing the samarium cobalt permanent magnetic material according to claim 1, characterized in that: The method for preparing the samarium-cobalt magnet alloy powder comprises the following steps: smelting and crushing the raw materials of the samarium-cobalt permanent magnet material.

8. The method for preparing the samarium cobalt permanent magnetic material according to claim 7, characterized in that: The smelting method is a belt casting method, a centrifugal casting method or an ingot casting method.

9. The method for preparing the samarium cobalt permanent magnetic material according to claim 7, characterized in that: The crushing methods include coarse crushing, medium crushing and fine crushing.

10. The method for preparing the samarium cobalt permanent magnetic material according to claim 9, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The coarse crushing includes jaw crushing; (2) The intermediate crushing includes crushing with a intermediate crusher and / or crushing with a disc mill; (3) The fine crushing includes air mill crushing and / or ball mill crushing.

11. The method for preparing the samarium cobalt permanent magnetic material according to claim 10, characterized in that: After the samarium-cobalt magnet alloy powder is jet milled or ball milled, the average particle size D50 is 4-6 μm.

12. The method for preparing the samarium cobalt permanent magnetic material according to claim 1, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The molding is performed by oriented pressing in a constant magnetic field; (2) The sintering is carried out in an inert atmosphere; (3) The sintering temperature is 1200-1220° C.; (4) The sintering time is 2 to 5 hours; (5) The sintering also includes solid solution.

13. The method for preparing the samarium cobalt permanent magnetic material according to claim 12, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The magnetic field strength B of the molding is 1.5 to 2 T; (2) The temperature of the solid solution is 1140-1190° C.; (3) The solution treatment time is 1 to 40 hours.

14. The method for preparing the samarium cobalt permanent magnetic material according to claim 1, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or both of the following conditions: (1) The primary aging temperature is T = (M1 × a + N1) ° C; wherein M1 is 20; N1 is 450; (2) The time of the primary aging is t=(M2×T+N2) min; wherein M2 is -10.00; N2 is 9700; and T is the temperature of the primary aging.

15. The method for preparing the samarium cobalt permanent magnetic material according to claim 14, characterized in that: The time of the primary aging is t=(-10×T+9700)min.

16. The method for preparing the samarium cobalt permanent magnetic material according to claim 1, characterized in that: The insulation temperature is 390-420°C.

17. The method for preparing the samarium cobalt permanent magnetic material according to claim 16, characterized in that: The preparation method of the samarium cobalt permanent magnet material meets one or more of the following conditions: (1) The insulation temperature is 400° C. (2) The insulation time is 5 to 10 hours; (3) The rate of decreasing from the primary aging temperature to the insulation temperature is 0.7°C / min.

18. A samarium cobalt permanent magnet material, characterized in that: The samarium cobalt permanent magnet material is prepared by the method for preparing the samarium cobalt permanent magnet material according to any one of claims 1 to 17.

19. A samarium cobalt permanent magnet material, characterized in that: The samarium cobalt permanent magnet material has a uniform and complete cellular organizational structure and a uniform and fine strip-shaped magnetic domain structure; the interior of the strip-shaped magnetic domain structure is in a maze shape.

20. The samarium cobalt permanent magnetic material according to claim 19, characterized in that: The domain width of the strip-shaped magnetic domain structure is 1.8-2.2 μm.

21. The samarium cobalt permanent magnetic material according to claim 20, characterized in that: The domain width of the strip-shaped magnetic domain structure is 1.9 μm, 2.0 μm or 2.1 μm.

22. Use of the samarium cobalt permanent magnet material according to any one of claims 18 to 21 in the preparation of electronic communication equipment, aerospace equipment or rail transportation equipment.

Citation Information

Patent Citations

  • 2-17 type samarium-cobalt permanent magnet material, and preparation method and application thereof

    CN113593882A